Limited Access to Information as a Means Of Censorship In Post-Communist Russia - de Smaele, Hedwig (Javnost-The Public, 2004)
Censorship in post-communist Russia is outlawed, while the right to information is legally guaranteed. In practice, however, access to information is a frequently mentioned problem for journalists and citizens alike. The information climate is still characterised by secrecy rather than openness. The buzzword of “confidential information” (commercial, state, or military secrets) replaces earlier references to political or ideological control but is equally open to wide interpretations. This article describes the limited access to information in Russia as a form of highly effective censorship. Although these means of censorship are not exclusively Russian, the article focuses on why Russia seems especially vulnerable to this kind of censorship. The concept of “information culture” is used to describe the (Russian) attitude towards information and towards the distribution of information based on the values of collectivism and particularism rather than individualism and universalism.